The association between political climate and trainees' supervision experiences and needs. Issue 2 (3rd July 2022) - McCarthy, Kevin S.; Capone, Carla; Davidtz, Jennifer; Solomonov, Nili
ABSTRACT: This study examined whether political climate influenced trainees' clinical work, supervisory experiences, and supervisory alliance. Data were collected from 366 trainees in a nationwide survey. Most trainees believed that the political atmosphere has affected clients to some degree. Over half reported political dialogue with supervisors, more often when political affiliation was similar. Supervisory alliances were most positive when trainees were aware of their supervisors' political beliefs, regardless of agreement. Trainees wanted supervisors to provide greater awareness of multicultural issues and political climate in their clinical work. We recommend that supervisors invite trainees to discuss political effects on their clinical work.